Perspective-Taking of the Defendant: Does Race Influence the Final Sentencing Verdict for Mock Jurors? - Pardo, Matthew A (2017)
The main objective of this study is to test whether there are disparities in a final sentencing verdict, of a guilty defendant that identifies as either African-American or Caucasian. Using a mock-jury design, participants were randomly assigned to the police report of Jamal Washington (representing the African-American defendant), or Greg Sullivan (representing the Caucasian defendant). Additionally, participants were randomly assigned to either take the perspective of the defendant or not to take the perspective of the defendant (control). This combination of race and perspective-taking as manipulations allows for the examination of the extent of racial schemas in courtroom settings through the measurements of empathy, leniency, perceived recidivism, retributive justice, and a final sentence. Furthermore, in order to better understand sentencing decisions for a guilty defendant, this study incorporates a forgiveness scale that includes measurements of self-forgiveness, forgiveness of others, and situational forgiveness. The inclusion of the forgiveness scale assessed if one’s ability to forgive a transgression (self, other, and/or situational) alters participants’ assessments of the guilty defendant. Results from the present study saw significant differences in the perspective-taking condition where perspective-takers shower higher levels of empathy, leniency and reductions in retributive justice than participants in the control group. Additionally, for the race condition participants granted the African-American defendant (Jamal) a significantly longer sentence than the Caucasian defendant (Greg). Furthermore, interaction between race and perspective-taking was non-significant. Lastly, for the forgiveness subscales (self, other, and situational), only other-forgiveness was significantly correlated to the dependent variables; though, other-forgiveness had a minimal influence on the dependent variables. The pattern of the current study suggests that perspective-taking is advantageous within mock-jury scenarios, though there also seemed to be a racial bias/out-group bias against Jamal. Furthermore, while the interaction of perspective-taking and race was non-significant, trends suggest that “Greg” benefitted more than “Jamal” from the effects of perspective-taking; thus, adding more potential evidence that racial/out-group was captured in the present study